2018
DOI: 10.1002/admi.201801062
|View full text |Cite
|
Sign up to set email alerts
|

Ti‐Substituted Keggin‐Type Polyoxotungstate as Proton and Electron Reservoir Encaged into Metal–Organic Framework for Carbon Dioxide Photoreduction

Abstract: multiple electrons and protons, and the long-lived electron-proton coupled intermediates. This is of particular importance for the gas-solid reactions involving only water and CO 2 systems. Metal-organic frameworks (MOFs) are promising photocatalysts in CO 2 reduction due to the high CO 2 adsorption, large surface areas, open and orderly pores and channels, and remarkable structural and functional designability. [6][7][8][9] Nevertheless, MOFs are typically poor electron and proton conductors owing to the low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 52 publications
0
51
0
Order By: Relevance
“…However, the use of PDF and d-PDF methods is still limited in the field of guest@MOF materials, with only a few reports, most of which concerning the adsorption of small molecules. 30,[23][24][25][26][27][28][29][30][31][32][33][34][35] To the best of our knowledge, the investigation of POM@MOF and (POM,cat)@MOF composites by differential PDF analysis is the first of the kind.…”
Section: Resultsmentioning
confidence: 99%
“…However, the use of PDF and d-PDF methods is still limited in the field of guest@MOF materials, with only a few reports, most of which concerning the adsorption of small molecules. 30,[23][24][25][26][27][28][29][30][31][32][33][34][35] To the best of our knowledge, the investigation of POM@MOF and (POM,cat)@MOF composites by differential PDF analysis is the first of the kind.…”
Section: Resultsmentioning
confidence: 99%
“…The authors observed an enhanced chemical and thermal stability after the embedding of POM and no POM leaching was noted during catalysis in several studies [40,41]. In one of these studies, Shuxia Liu's group prepared a series of Keggin-type POMs in Cu-BTC, denoted as NENU-n, n = 1~10, and formulated as [Cu 2 (BTC) 4 2 (X = Si, Ge, P, As, V, Ti; M = W, Mo), by using a one-pot hydrothermal synthesis [42,43]. The templating effect of the POMs resulted in highly crystalline composite materials which showed an enhanced thermal stability.…”
Section: Introductionmentioning
confidence: 99%
“…The Au NPs were in-situ deposited during the assembly of NENU-10 and NENU-3 as shown in Figure 7.) was recently achieved [45]. Table 2 illustrated the catalytic performance of as-prepared hybrid in the reductive CO 2 transformation to CO and CH 4 under visible-light irradiation.…”
Section: Photocatalytic Co2 Reductionmentioning
confidence: 99%
“…The SEM images for Au@NENU-3 and Au@NENU-10, respectively (h, i). Reprinted with permission from [45]. Copyright © 2018 Wiley-VCH Verlag GmbH and Co. KGaA.…”
Section: Figures Schemes and Tablesmentioning
confidence: 99%